Pathogenesis of IgA Vasculitis: An Up-To-Date Review - Song, Yan; Huang, Xiaohan; Yu, Guizhen; Qiao, Jianjun; Cheng, Jun; Wu, Jianyong; Chen, Jianghua (Frontiers in Immunology, 2021)
Immunoglobin A (IgA) vasculitis (IgAV), formerly called the Henoch-Schönlein purpura (HSP), is a small vessel vasculitis, characterized by IgA1-dominant immune deposition at diseased vessel walls. IgAV is the most common form of vasculitis in children; typical symptoms include palpable purpura, arthritis or arthralgia, abdominal pain, and hematuria or proteinuria. Galactose-deficient IgA1 is detected in the tissues of the kidney and skin in patients with IgAV; it forms immune complexes leading to subsequent immune reactions and injuries. This report provides the recent advances in the understanding of environmental factors, genetics, abnormal innate and acquired immunity, and the role of galactose-deficient IgA1 immunocomplexes in the pathogenesis of IgAV.